International evaluation of neutron cross-section standards - Badikov, S. A. (Vienna, [Austria] : International Atomic Energy Agency, 2007)
Cross-section standards are required to be of high quality and accuracy to form the foundation of a wide range of important nuclear measurements and evaluations for both energy and non-energy applications. They constitute the yardstick for all other nuclear physics measurements. These standards have been re-assessed and evaluated to make significant improvements in the data, and to take into account important new experimental data and improved evaluation techniques. The methods employed were the most sophisticated ever used in cross-section evaluations. These present standards are more accurate than all earlier versions, and the given errors are well justified in the context of contemporary data and evaluation methodology. --Publisher's description.
Introduction / A.D. Carlson -- Evaluation methodology and codes / V.G. Pronyaev ... [y otros trece] -- The experimental database / A.D. Carlson ... [y otros tres] -- Microscopic nuclear models and light element standard cross-sections / H.M. Hofmann, G.M. Hale -- R matrix theory and light element standards evaluation / G.M. Hale ... [y otros cuatro] -- Perspectives on Peelle's pertinent puzzle / D.L. Smith ... [y otros seis] -- Results of the evaluation : comparisons with previous standards and experimental data / V.G. Pronyaev .. [y otros trece] -- Resulting standards data / V.G. Pronyaev ... [y otros trece] -- Justification for recommended uncertainties / V.G. Pronyaev ... [y otros trece].
STI/PUB/1291
Incluye referencias bibliográficas.
Available both in print and online.
Keywords: NEUTRONES -- EVALUACION; SECCION EFICAZ (FISICA NUCLEAR) -- EVALUACION